Values in the War for Peace: Wilson‘S New Order on the Pages of „Mir“ Newspaper – National or Corporate Doctrines? - Aneva, Nadelina (Media and Language, 2021)
The article examines the political discourse of Wilson’s Peace in the „Bulgarian Times”, as „Mir” newspaper is called. The method of content analysis was used, and the period under study is from the signing of the armistice in 1918 to the Paris Peace Conference in 1919. If Wilson’s peace is a „semiotic figure“ by Lotman’s definition, the question arises why he failed to translate it into comprehensible language of the negotiating table its draft post-war order. One of the problems I find on the pages of the “Mir” newspaper is the lack of deciphering codes, as Europe and America meant war and peace in different ways. For Wilson, as well as for the Mir newspaper, there is a good war and a good peace. The Bulgarian tragedy by Neuilly led to a discrepancy in the meanings of words that are of different order – words from the old and words from the new world order.
Keywords: Wilson’s Peace; discourse; „Mir” newspaper; content analysis; semiosis